Order, complexity, measure. The project between architecture and nature - Antonella Falzetti; Ina Macaione; Vera Autilio (Agathón)
The paper aims to show how modern technologies, including those coming from established habits – today with great possibilities – have shifted towards new building horizons with an ‘ecological conscience’, avoiding uncritically referring to nature as a salvific model, to be imitated and evoked, perhaps with formal and superficial operations. The paper contains some varied project experiences. Even though the projects start from different premises, they develop experimental solutions identifying nature as a principle to elaborate by updating its rules. Among these, we find both a prototype of urban micro-design that incorporates vegetal processes and rules its aesthetic and functional benefits, where nature is integrated into the building technique, and projects with an indigenous origin important for the implementation of the symbiosis between nature and architecture in the built environment.